Theoretical Chemistry in Belgium A Topical Collection from Theoretical Chemistry Accounts - Champagne, Benoît; Deleuze, Michael S.; De Proft, Frank; Leyssens, Tom (Highlights in Theoretical Chemistry, 2014)
Readers of this volume can take a tour around the research locations in Belgium which are active in theoretical and computational chemistry. Selected researchers from Belgium present research highlights of their work. Originally published in the journal Theoretical Chemistry Accounts, these outstanding contributions are now available in a hardcover print format. This volume will be of benefit in particular to those research groups and libraries that have chosen to have only electronic access to the journal. It also provides valuable content for all researchers in theoretical chemistry.